TraceTogether: Pandemic Response, Democracy, and Technology. Issue 3 (1st September 2020) - Stevens, Hallam; Haines, Monamie Bhadra
Abstract: On 20 March 2020, in the midst of the COVID-19 pandemic, the Singapore government released a new app called TraceTogether. Developed by the Ministry of Health, SG United, and GovTech Singapore, the app uses the Bluetooth capability of smartphones to store information about other smartphones that have come into close proximity with your own. These data facilitate the government's process of "contact tracing" through which they track those who have potentially come into contact with the virus and place them in quarantine. This essay attempts to understand what kinds of citizens and civic behavior might be brought into being by this technology. By examining the workings and affordances of the TraceTogether app in detail, the authors argue that its peer-to-peer and open-source technology features mobilize the rhetorics and ideals of citizens science and democratic participation. However, by deploying these within a context that centralizes data, the app turns ideals born of dissent and protest on their head, using them to build trust not within a community but rather in government power and control. Rather than building social trust, TraceTogether becomes a technological substitute for it. The significant public support for TraceTogether shows both the possibilities and limitations of citizen science in less liberal political contexts and circumstances.